Bayesian quantile regression for semiparametric models - Hu, Yuao (2013)
Quantile regression has recently received a great deal of attention in both theoretical and empirical research. It can uncover different structural relationships between covariates and responses at the upper or lower tails, which is sometimes of significant interest in econometrics, educational and medicine applications. The methodologies of quantile regression for linear models have been well developed in both frequentist and Bayesian contexts. However, there has been relatively less work focusing on quantile regression for nonparametric models or semiparametric models, especially from a Bayesian perspective.